Metabolismo secundário de fungos endofíticos do gênero Penicillium associados às plantas Murraya paniculata (Rutaceae) e Melia azedarech (Meliaceae) - Marinho, Andrey Moacir do Rosário (Universidade Federal de São Carlos, 2005)
The Penicillium sp. A, Penicillium sp. B (M. paniculata) and P. herquei (M. azedarach) fungus were grown in liquid media (Czapeck s) and also in solid media (rice). After the inoculation of the fungus, their grownth were interrupted by adition of methanol. The extracts of the biomass were obtained by several maceration technics using organic solvents. The crude extracts were fractionated by liquid-liquid partition and also several chromatography technics. The pure compounds were obtained by refractionation of previous fractions by column chromatography, thin layer chromatography and HPLC. The structures of the compounds were elucidated by several spectroscopic technics as NMR, MS and IR. Several classes of compounds were isolated as nucleosides, esteroids, carbohydrates, polyketides among many others. Antimicrobial assays were carried out with purified compounds, where the polyketides citrinine, citrinine-D, citrinine H1, emodine, citreoroseine and janthinone showed promising results. Leishmanicidal assays were also carried out using emodine, citreoroseine and janthionone, where only the former showed a reasonable activity. The fragmentation by MS and also the biogenesis proposal of some isolated compounds are discussed in the present work.
Secondary metabolism of endophytic fungus from Penicillium genus associated to Murraya paniculata (Rutaceae) and Melia azedarach (Meliaceae) plants
Keywords: Produtos naturais; Fungos endofíticos; Metabolismo secundários de fungos; Penicillium; Murraya paniculata; Melia azedarach; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS